2001 Conference Proceedings of the 23rd Annual International Conference of the IEEE Engineering in Medicine and Biology Society
DOI: 10.1109/iembs.2001.1019082
|View full text |Cite
|
Sign up to set email alerts
|

Magnetic nerve stimulation: field focality and depth of penetration

Abstract: Subject Terms Report Classification unclassified Classification of this page unclassified Classification of Abstract unclassified Limitation of Abstract UU Number of Pages

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 9 publications
0
8
0
Order By: Relevance
“…Other designs for deep brain TMS coils have been proposed, such as the stretched C-shaped ferromagnetic core coil, 3,68,97 circular crown coil, 3 and large halo coil. 98 The halo coil has been shown to elicit lower limb and trunk muscle contractions in a cynomolgus monkey, suggesting that this coil design is capable of directly stimulating relatively deep brain regions.…”
Section: Introductionmentioning
confidence: 99%
“…Other designs for deep brain TMS coils have been proposed, such as the stretched C-shaped ferromagnetic core coil, 3,68,97 circular crown coil, 3 and large halo coil. 98 The halo coil has been shown to elicit lower limb and trunk muscle contractions in a cynomolgus monkey, suggesting that this coil design is capable of directly stimulating relatively deep brain regions.…”
Section: Introductionmentioning
confidence: 99%
“…Based on analysis and simulations, it was suggested that a C-shaped ferromagnetic core coil with a wide opening angle (Figure 1(b)) can suppress the surface field and, consequently, could reduce scalp stimulation (Davey, 2008; Davey and Riehl, 2006; Al-Mutawaly et al, 2001). It is unclear whether the addition of ferromagnetic cores is practical as they might enter magnetic saturation in the field range needed for dTMS.…”
Section: Introductionmentioning
confidence: 99%
“…In other words, it denotes the maximum distance beneath the coil that the electric field can exceed neuron excitation threshold. Studies have shown that the threshold approximately meets the equation (5) and the variables are defined in TABLE.I [10][11]:…”
Section: Evaluation Of Stimulation Depthmentioning
confidence: 99%
“…But efficiency is not much concerned in practice. Although quite amount of work [5][6][7][8] has been done to investigate the stimulation effect both from TMS devices and biological-effect aspects, there has no unified evaluation criterion for TMS devices, which is of great importance to assess the stimulation effect quantitively instead of vague expression such as µbetter ¶ or µworse ¶. In this paper, preliminary work has been done to propose several indexes which can be used as design guidelines for TMS devices and performance comparison as well.…”
Section: Introductionmentioning
confidence: 99%